Potential of Bacterial Inoculants to Mitigate Soil Compaction Effects on Gossypium hirsutum Growth - Fausto Henrique Viera Araújo; Crislaine Alves da Conceição; Adriene Caldeira Batista; Gabriel Faria Parreiras de Andrade; Caique Menezes de Abreu; Paulo Henrique Grazziotti; Ricardo Siqueira da Silva (Plants)
Aims: Soil compaction is one of the main challenges in agriculture, negatively affecting cotton growth (Gossypium hirsutum L.), nutrition, and productivity. This study evaluated the efficacy of plant growth-promoting bacteria (PGPB), Exiguobacterium sibiricum, and Pantoea vagans in mitigating the effects of different soil compaction levels (65%, 75%, 85%, and 95%) on cotton performance. Methods: Parameters such as plant height, stem diameter, number of leaves, shoot dry matter (SDM), and nutrient content in leaves, stems, and roots were assessed. The methodology included variance analysis and mean clustering to identify significant differences among treatments using R software. Results: The results indicated that PGPB inoculation improved plant growth and nutrition even under high compaction levels. Cotton height increased by up to 45% in compacted soils (95%), while stem diameter and SDM also showed significant gains. Foliar nutrient levels of N (37.2 g kg−1), Ca, and Mg remained within the adequate range for cotton cultivation, reflecting the efficiency of PGPB in enhancing nutrient absorption. Under severe compaction, Ca accumulation dropped to 18.2 g kg−1, highlighting the physical constraints imposed on the roots; however, the bacterial action mitigated this impact. Additionally, bacterial strains increased the availability of N and P in the soil due to their ability to fix nitrogen, solubilize phosphates, and produce exopolysaccharides that improve soil structure. Conclusions: In conclusion, inoculation with Exiguobacterium sibiricum and Pantoea vagans is an effective strategy to mitigate the impacts of soil compaction on cotton. These bacteria promote plant growth and nutrition and enhance the soil’s physical and biological properties.